The risk factors of procedure-related complications after amniocentesis in twin pregnancies: a retrospective analysis - Xijing Liu; Jiamin Wang; Wanying Luo; Qiyi Wang; Zhushu Liu; He Wang; Shanling Liu; Ting Hu (BMC, 2023)
Abstract Background There is an increasing demand for prenatal diagnostic testing in twin pregnancies, however, anecdotally there is a higher incidence of procedure-related complications after amniocentesis than that in singleton pregnancies. There is a paucity of data regarding risk factors of amniocentesis in twin pregnancies. Methods Women with twin pregnancies who underwent amniocentesis between January 2016 and December 2020 were enrolled in this retrospective study. Procedure-related complications including spontaneous miscarriage, intrauterine fetal death, spontaneous preterm delivery, preterm premature rupture of membranes, and placental abruption in one or both fetuses after amniocentesis were assessed. Meanwhile, potential risk factors related to amniocentesis including chorionicity, gestational age, conception, number of needle insertions, parity, history of miscarriage, indications, and pregnancy-related complications (pregnancy-induced hypertension and gestational diabetes) were also recorded. Results A total of 811 women with twin pregnancies underwent amniocentesis were included, with a procedure-related complications rate of 3.83%. Risk factors associated with increased risk of procedure-related complications after amniocentesis in twin pregnancies were chorionicity (adjusted odds ratio [aOR]: 4.06), gestational age at the procedure (aOR: 2.76), and numbers of needle insertions (aOR: 3.26). In the monochorionic twin pregnancy, hemorrhage during this pregnancy (aOR: 12.01), polyhydramnios (aOR: 5.03), and numbers of needle insertions (aOR: 3.15) were risk factors after amniocentesis. In the dichorionic twin pregnancy, gestational age at the procedure (OR:4.47) affected the risk of procedure-related complications after amniocentesis. In the subgroup of gestational age at the procedure ≤ 24+ 0 weeks, risk factors associated with increased risk of procedure-related complications after amniocentesis in twin pregnancies were chorionicity (aOR: 5.14), and numbers of needle insertions (aOR: 3.76). Conclusion The procedure-related complications rate is 3.83% in our institution during the study period. The present study has emphasized the significance of certain risk factors for adverse outcome and will be useful in counseling patients with twin pregnancies.